Population organization and ranging pattern of Rhesus macaque (Macaca mulatta) at Bandar, Narayanganj - Shoma, Shamia Farhana; Feeroz, Mohammed Mostafa (Jahangirnagar University Journal of Biological Sciences, 2016)
A study was conducted on population organization and ranging pattern of rhesus macaque at Bandar Upazila, Narayanganj, Dhaka from December, 2009 to September, 2010. Direct count method was used to study the group size and composition, and ranging was determined by GPS coordination plotting on the map. A total of 66 monkeys (29 to 37 individuals) were found in two groups with a mean of 33±5.6. Among the population 7.6% adult male, 33.3% adult female, 9.1% sub-adult male, 7.6% sub-adult female, 25.8% juvenile and 16.7% was infant. The ratio between adult male and adult female was 1:4.4 and between adult and nonadults was 1:1.4. Day range length varied from 1543m to1716m (mean=1638.43±56.7). Home range was completely overlapped and varied negligibly from 45.2 ha. to 45.5 ha. (mean=45.32±0.2). They minimized conflictions by using different time to move. But the growing dependence of these urban macaques on human resources is a matter of concern. Therefore, conservation strategies should be directed to minimize this dependence. Jahangirnagar University J. Biol. Sci. 3(1): 27-35, 2014 (June)